Pengembangan Mobile Learning Untuk Penguasaan Mufrodat Siswa MTs - Koderi, Koderi; Aridan, Muhammad; Muslim, Ahmad Bukhari (Institut Agama Islam Negeri Curup, 2020)
This study aims to develop Arabic language teaching media based on mobile learning and to determine the feasibility and influence of the developed media on student learning outcomes. Hannafin and Peck's development model is the model used in this study. Needs analysis, design, development and implementation are the stages in this research. This study involved material experts and media experts as validators. This study produces Arabic language teaching media products with mufrodat material based on mobile learning for Madrasah Tsanawiyah (MTs) with an offline operational system using a smartphone (Android). The feasibility of this product is classified in the very feasible category with a percentage score of 93% by material experts, 96.25% by media experts, 93% one on one trial, 86% small group trials, 92% by large group trials (field trials). Based on the results of calculations with the T-test, the value obtained t0 = 62.5> t table = 2.093 with a difference in learning outcomes reaching 38.75. Thus the media for teaching Arabic lessons on the basis of mobile learning, the developed mufrodat material is very effective and also very suitable for use in learning Arabic.